Atrial fibrillation screening in Syrian patients reporting to the emergency department during the ongoing conflict: a cross-sectional study - Antoun, Ibrahim; Alkhayer, Alkassem; Jalal Eldin, Aref; Alkhayer, Alamer; Salama, Ibrahim; Yazji, Khaled; Somani, Riyaz; Ng, G. André; Zakkar, Mustafa (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAtrial fibrillation (AF) is the most common arrhythmia worldwide. Data regarding AF screening in conflict countries’ emergency departments (ED) is lacking.MethodsWe included consecutive patients >40 years old who reported to the ED of a Syrian tertiary centre between July 2024 and September 2024. Patients had routine 12-lead electrocardiograms (ECGs) regardless of presenting complaints. Two cardiology consultants blindly verified ECG findings. We excluded critically unwell patients and ECG discrepancies between the two consultants. Data were taken from patients’ medical notes.ResultsThe final analysis included 694 patients, 101 (15%) had AF on the ECG. The most common presenting complaints and ECG abnormality were trauma (44%) and sinus tachycardia (15%), respectively. Compared to the rest of the patients, AF patients were older (66 vs. 59 years; p < 0.001), had a lower proportion of males (39% vs. 54%; p = 0.01), a higher prevalence of diabetes mellitus (49% vs. 21%; p = 0.01), and more cases of congestive cardiac failure (CCF) (38% vs. 17%; p < 0.001). AF patients also had a higher CHA₂DS₂-VASc score (3 vs. 2; p < 0.001). CCF [odds ratio [OR]: 3.3, 95% confidence interval [CI]: 1.5–6.4, p < 0.001] and a higher CHA₂DS₂-VASc score(OR: 4, 95% CI: 1.6–7.7, p < 0.001) were independently associated with positive AF screening.Conclusion15% of patients reporting to this Syrian ED had positive AF screening. CCF and CHA₂DS₂-VASc scores are predictive of AF.